AN EMPIRICAL ANALYSIS OF THE RELATIONSHIP BETWEEN TECHNOLOGICAL AND MARKETING INNOVATIONS : A CASE OF POLISH MANUFACTURING FIRMS - Kijek, Tomasz (Acta Scientiarum Polonorum. Oeconomia, 2013)
The article deals with the issue of the links between technological and marketing innovations. The theoretical part of the paper presents definitions and key features of marketing innovations, as well as it indicates the potential cause-effect relations between decisions to introduce process and product innovations and the implementation of new methods in marketing mix. The empirical part of the paper verifies formulated hypotheses using data derived from the survey on innovation activity of Polish manufacturing enterprises in the years 2008-2010. The results of research show the positive impact of propensity to adapt product innovations on marketing innovations activity of enterprises. Moreover, expenditures on acquisition of knowledge from external sources and expenditures on marketing for new and significantly improved products turned out to be factors stimulating enterprises to implement changes in marketing methods.